(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Swamiji, a man of extraordinary learning, was a true bibliophile. Wherever he went on all his travels abroad, he visited libraries and wrote back home about them in glowing terms. In spite of his love of books, he never equated reading with either learning or moral and spiritual progress, reiterating that spiritual advancement and enlightenment did not depend on book learning but had its source in our own psyche.Keywords Swami Vivekananda, Libraries, Knowledge, Education, Learning, Religion.The aim of this paper1.A short biography of Swami Vivekananda and a discussion on it.2.Swami Vivekananda’s views on libraries.3.The relevance today of what Swami Vivekananda says about libraries.Methodology A scrutiny of all his writings, especially his letters.Findings While Swami Vivekananda speaks about the overwhelming importance of books and libraries, he also stresses that books alone cannot make a man spiritually cultivated.Originality This paper looks for the first time at the role of libraries in Swamiji’s life.